THE USE OF ADOBE ANIMATE AS A NEW TECHNOLOGY IN TEACHING ACADEMIC ESSAY WRITING IN DARMA PERSADA UNIVERSITY - Yoga Pratama; Endry Boeriswati; Fathiaty Murtadho (English Education Department, 2020)
Abstract The development of information and technology has affected many aspects of life including education. Writing has an important role in the language academic process. Technology also gives a positive effect toward the students’ motivation in learning English, especially in essay writing. Nowadays, a computer technology application is developing writing materials by using adobe animate. The purpose of this research is to show that the role of technology today is very important in learning process specifically in teaching academic writing, so that it can help teacher and students to make lots variations in teaching. In the past, teaching writing only used conventional ways like books but nowadays teachers and students can use multimedia technology like education interactive software, smartphone, and computer which can make studying more effective and interactive. In this qualitative research the writers will analyse and demonstrate the new technology as a solution to the old problem of teaching academic essay writing.